Faktor-faktor yang mempengaruhi kunjungan wisatawan mancanegara ke Provinsi Jambi - Guntur Guntur; Aulia Tasman (e-Jurnal Perspektif Ekonomi dan Pembangunan Daerah, 2015)
This study aims to analyze: 1) the development of tourism in Jambi Province, especially foreign tourist visits; 2) factors that influence foreign tourist visits to Jambi Province, especially in Kerinci District and Muaro Jambi Regency. The data used are primary data and secondary data. Primary data comes from tourism stakeholder key informants and foreign tourist respondents. The main secondary data was sourced from the Jambi Province Culture and Tourism Agency, Kerinci Regency and Muaro Jambi Regency. Data were analyzed descriptively quantitatively and qualitatively. The results of the study found: 1) Jambi Province with its natural beauty and cultural diversity and historical heritage has not shown a relatively high development in terms of tourist visits to Jambi Province, especially foreign tourists; 2) The lack of foreign tourist visits to Jambi Province is caused by the lack of tourism information available on the Jambi tourism website, so that the limited information obtained by foreign tourists for their trips. The poor tourism support infrastructure in Jambi Province and the lack of reliable and certified guides in Jambi Province.